Study and Design of a SCADA System for Controlling and Predicting Faults of Conveyors for the Tobacco Factory in Lattakia - عبد الرحمن, نزار; نعمان, زياد; عبدالله, علي (Latakia University Journal -Engineering Sciences Series, 2022)
With the expansion of quantitative and geographical industrial work it was necessary to find new method of control or develop existing method to improve the required performance . The research focus on the development of tobacco factory control system in the city of Latakia which is currently based on the programmable controller PLC, where the factory is controlled automatically without any contact with the user or monitor to find any data o the different stages of work from the beginning where the tobacco is raw and the end to reach readymade cigaretts ,among the most important control systems that have emerged In recent times are supervisory control system SCADA (supervisory control and data acquisition system) wich will be the subject of our research. The research dealt wihe the study ad analysis of the existing system to determine its components, study the algorithms used, and then find the appropriate mechanisms to transform the control mechanism of this lab into an integrated control system and a communication interface. The research used the SCADA supervisory control and data acquisition system because it meets all the requirements of users and operators through communication between the user and the operating and management device, in addition to the sufficient ability that this system gives to control precisely and in an ordely manner the entire production process from beginning to end , in addition early detection of malfuctios and alarms that predict their occurrence thuse ensuring the best reliability of the system and work .